Pre-emptive Analgesia for Postoperative Pain Relief in Children Role of Paracetamol (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
This prospective clinical study was carried out in the Dept. of Anaesthesia, Analgesia and Intensive Care Medicine, BSMMU, Dhaka, during the period of May 2003 to July 2003. The study was done to emphasize the importance of giving analgesics preemptively instead of waiting for the child to complain of pain and to produce smooth recovery after surgery by decreasing immediate postoperative pain in children by a simple, safe acceptable drug. The children scheduled for tonsillectomy under general anaesthesia were recruited in this study. The analgesic efficiency of rectal paracetamol in two doses, 25 mg/kg bodywt.(Gr-P25) and 50 mg/kg. bodywt. (Gr-P50) were compared with Diclofenac Sodium suppository 1mg/ kg body weight (Gr-D) given half an hour before induction of anaesthesia. Pain scoring was done by TPPPS (Toddler Pre-schooler postoperative pain scale). Heart rate and blood pressure were stable in Gr-P50 and Gr-D. Time of first demand of analgesic was delayed in Gr-P50 and Gr-D. Total paracetamol consumption in 24 hours was less in Gr-P50(181±14.25) and Gr-D (212±25) than Gr-P25(318± 26.39). Total duration of analgesia in Gr- P50 (657±9.94) mins. and in Gr- D(502±10.63) mins. and in Gr-P25(288±23.17) mins. Pre-emptive high dose rectal paracetamol appears to be more effective than diclofenac sodium suppository for postoperative analgesia in children undergoing tonsillectomy. Journal of BSA, Vol. 18, No. 1 & 2, 2005 p.9-16